2016
DOI: 10.1016/j.neuroscience.2016.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional connections between the locus coeruleus and the nucleus tractus solitarius in neonatal rats

Abstract: This study was designed to investigate brain connections among chemosensitive areas in newborn rats. Rhodamine beads were injected unilaterally into the locus coeruleus (LC) or into the caudal part of the nucleus tractus solitarius (cNTS) in Sprague-Dawley rat pups (P7–P10). Rhodamine-labeled neurons were patched in brainstem slices to study their electrophysiological responses to hypercapnia and to determine if chemosensitive neurons are communicating between LC and cNTS regions. After 7–10 days, retrograde l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 96 publications
(168 reference statements)
2
21
0
Order By: Relevance
“…Discussions of the possible functional significance of brain studies customarily reference electrophysiological or pharmacological articles related to specific anatomical sites or connections. For example, recent literatures have highlighted chemistry of NTS-PVH and NTS-LC connections (Affleck et al, 2012 ), central and peripheral chemoreception mechanism involving several brainstem regions such as NTS, LC, respiration-related areas and raphe (Kumar and Prabhakar, 2012 ; Nattie and Li, 2012 ; Guyenet, 2014 ; Lopes et al, 2016 ), and food intake/energy expenditure, appetite control by cholecystokinin concerned with NTS-PVH projection (Rinaman, 2010 ; D’Agostino et al, 2016 ). However, this is not the case in the present study, as the focus is not analytical or reductionist but rather a gestalt or holistic view of homeostatic control of the whole body to describe a possible underlying network system.…”
Section: Discussionmentioning
confidence: 99%
“…Discussions of the possible functional significance of brain studies customarily reference electrophysiological or pharmacological articles related to specific anatomical sites or connections. For example, recent literatures have highlighted chemistry of NTS-PVH and NTS-LC connections (Affleck et al, 2012 ), central and peripheral chemoreception mechanism involving several brainstem regions such as NTS, LC, respiration-related areas and raphe (Kumar and Prabhakar, 2012 ; Nattie and Li, 2012 ; Guyenet, 2014 ; Lopes et al, 2016 ), and food intake/energy expenditure, appetite control by cholecystokinin concerned with NTS-PVH projection (Rinaman, 2010 ; D’Agostino et al, 2016 ). However, this is not the case in the present study, as the focus is not analytical or reductionist but rather a gestalt or holistic view of homeostatic control of the whole body to describe a possible underlying network system.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was assessed by twoway ANOVA followed by Bonferroni's post hoc tests compared to vehicle (**p < 0.01; ***p < 0.001; n 5 7-8/group) ALBERINI ET AL. | 1251 Summers, 2010;Lopes et al, 2016;Sara, 2009;Sara, Vankov, & Herve, 1994).…”
Section: Gl Ycog En Oly Si S a Nd L A Cta Te A Re I M P O Rta N T Imentioning
confidence: 99%
“…Having shown that noradrenergic LC cell activity is required for LTF expression, we next wanted to identify a mechanism by which recurrent apneas recruit and activate LC cells. Because vagal feedback is required for apnea-induced LTF 4 and because vagal afferents terminate in the NTS 11 and project to and modulate LC activity 24 , 25 , we hypothesized that the NTS is required for triggering apnea-induced LTF. Therefore, we pharmacologically inactivated cells in the NTS by bilaterally injecting lidocaine into the left and right NTS before repeatedly occluding the airway.…”
Section: Resultsmentioning
confidence: 99%